Uptake of HIV testing among adolescents and associated adolescent-friendly services - Rachel Kidman; Jennifer Waidler; Tia Palermo; On Behalf of the Tanzania Adolescent Cash Plus Evaluation Team (BMC, 2020)
Abstract Background HIV testing remains low among adolescents. Making public health services more adolescent-friendly is one strategy used to encourage testing. However, it remains unclear whether government-led initiatives have a meaningfully impact. Methods The current study is observational and utilizes two sources of data (health-facility and adolescent-level) from one round of data collection of an on-going, longitudinal impact evaluation of a pilot cash plus program targeting adolescents. This study linked data from adolescent surveys (n = 2191) to data collected from nearby government-run health facilities (n = 91) in two rural regions of Tanzania. We used log binomial regression models to estimate the association between specific adolescent-friendly health service (AFHS) characteristics and adolescents' uptake of 1) HIV testing and 2) visiting a health care facility in the past year for sexual and reproductive health (SRH) services. Results Most adolescents (67%) lived in a village with a health facility, and all offered HIV services. We find, however, that AFHS have not been fully implemented. For example, less than 40% of facilities reported that they had guidelines for adolescent care. Only 12% of facilities had a system in place for referral and follow-up with adolescent clients, yet this was an important predictor of both past-year HIV testing (RR = 1.28, p < 0.1) and SRH visits (RR = 1.44, p < 0.05). Less than half (44%) offered services for survivors of gender-based violence (GBV), a significant predictor of past-year HIV testing (RR = 1.20, p < 0.05) and SRH visits (RR = 1.41, p < 0.01) among sexually-active adolescents. Conclusions We find that national guidelines on AFHS have not been fully translated into practice at the local level. We highlight particular gaps in adolescent referral systems and GBV services. Scaling up these two essential services could encourage greater HIV testing among a high-risk population, in addition to providing much needed support for survivors of violence.